Primary ciliary dyskinesia diagnosis and management and its implications in America: a mini review - Castillo, M.; Freire, E.; Romero, V. I. (Frontiers in Pediatrics, 2023)
Primary ciliary dyskinesia (PCD) is a rare genetic disorder that can result in significant morbidity and mortality if left untreated. Clinical manifestations of PCD include recurrent respiratory infections, laterality defects, and infertility, all of which arise from impaired or absent ciliary motility. Diagnostic approaches for PCD may include highspeed video microscopy, measurement of nasal nitric oxide levels, and genetic testing; however, no single definitive diagnostic test exists. The present study aims to highlight the lack of standardized diagnostic and treatment guidelines for PCD in Latin America (Central and South America, and the Caribbean). To this effect, we compared North American and European recommendations for the diagnosis and management of PCD and found that certain diagnostic tools and treatment options mentioned in these guidelines are not readily accessible in many Latin American countries.This review gathers disease information in North America, Europe, and Latin America organizing guideline results into tables for clarity and potential interventions.Management information for Latin America is inferred from case reports, as most findings are from North American recommendations and studies on PubMed, Google Scholar, and Scopus. Treatment and management information is based on North American and European standards.Among 5774 publications reviewed, only 15 articles met the inclusion criteria (focused on PCD management, peer-reviewed, and located in America). No clinical guideline for PCD in Latin America was found, but recommendations on respiratory management from Colombia and Chile were discovered. The lack of guidelines in Latin America may originate from limited resources and research on the disease in those countries.PCD lacks documentation, research, and recommendations regarding its prevalence in Latin America, likely due to unfavorable economic conditions. This disadvantage results in limited access to diagnostic tests available in North America and Europe. The PICADAR score, discussed in this review, can be used in low-income nations as a screening tool for the disorder.